The WHO-INTEGRATE evidence to decision framework version 1.0: integrating WHO norms and values and a complexity perspective. (28th January 2019) - Rehfuess, Eva A; Stratil, Jan M; Scheel, Inger B; Portela, Anayda; Norris, Susan L; Baltussen, Rob
Abstract : Introduction: Evidence-to-decision (EtD) frameworks intend to ensure that all criteria of relevance to a health decision are systematically considered. This paper, part of a series commissioned by the WHO, reports on the development of an EtD framework that is rooted in WHO norms and values, reflective of the changing global health landscape, and suitable for a range of interventions and complexity features. We also sought to assess the value of this framework to decision-makers at global and national levels, and to facilitate uptake through suggestions on how to prioritise criteria and methods to collect evidence. Methods: In an iterative, principles-based approach, we developed the framework structure from WHO norms and values. Preliminary criteria were derived from key documents and supplemented with comprehensive subcriteria obtained through an overview of systematic reviews of criteria employed in health decision-making. We assessed to what extent the framework can accommodate features of complexity, and conducted key informant interviews among WHO guideline developers. Suggestions on methods were drawn from the literature and expert consultation. Results: The new WHO-INTEGRATE (INTEGRATe Evidence) framework comprises six substantive criteria— balance of health benefits and harms, human rights and sociocultural acceptability, health equity, equality and non-discrimination, societal implications, financial and economic considerations, and feasibility and health system considerations —and the meta-criterion quality of evidence . It is intended to facilitate a structured process of reflection and discussion in a problem-specific and context-specific manner from the start of a guideline development or other health decision-making process. For each criterion, the framework offers a definition, subcriteria and example questions; it also suggests relevant primary research and evidence synthesis methods and approaches to assessing quality of evidence. Conclusion: The framework is deliberately labelled version 1.0. We expect further modifications based on focus group discussions in four countries, example applications and input across concerned disciplines.